Tradycja katechizmów i podręczników katechetycznych w Wielkopolsce - Szpet, Jan (Poznańskie Studia Teologiczne, 2018)
The 1050 anniversary of the first bishopric in Poznań has become an opportunity to reflect on the contribution of the representatives of Great Poland to catechetical activity in Poland. The article presents several outstanding personages and their works: catechisms as well as textbooks for cat- echesis and religious education. The circumstances in which these works were created and their merits are described.